Managemen Topikal Anti-Aging pada Kulit - Winda Puspita Sari; Meligasari L.Gaya; Galih Irianto; Nisa Karima (CV. Jasa Sukses Abadi, 2019)
The Aging skin is a complex biological process involving endogenous or intrinsic factors (genetics, cellular communication, hormones, and mining processes) and exogenous or extrinsic factors (explanation of light, radiation, ionizing radiation, chemicals, and diverted) which are structural changes and cumulative physiological and progressive changes in each layer of the skin and changes in the appearance of the skin such as wrinkles and spots.These factors cause oxidative stress on the skin which triggers damage to cells and skin tissue. At present it is very popular to use anti-aging products. Anti-aging approach is based on the pathophysiology that occurs. So that care can be given to work optimally. Anti-aging can be done using cosmetic treatments, topical agents that contain anti-oxidants and cell regulators. In addition to topical treatments, it can be given systemically or invasively. In this review we will discuss topical anti-aging treatments.